Peer Feedback Through Facebook Group; Does It Bring about Effect on Students' Writing Competence at MAN 1 Konawe Selatan - Saputra, Aksan; Lio, Asrun; Muhsin, Muhammad Khusnun (Journal of Teaching English, 2019)
This research is aimed at investigating whether or not there was a significant effect of Peer Feedback through Facebook Group on students’ writing competence at MAN 1 Konawe Selatan in writing recount text. The design of this research was pre-experimental design which involved only one class (class X MIA 1) as sample of this research. The total sample was 24 students which selected by using purposive sampling technique. The instrument of this research was a written test which focused on three aspects of writing namely organization, language use and mechanics. The researcher collected the data by giving pre-test and post-test in order to know students’ writing competence before and after treatment of Peer Feedback through Facebook Group had been applying. The researcher used the paired sample t-test in SPSS 16 Windows Software to analyze the result of this research. The finding shows that there is a significant effect of Peer Feedback through Facebook Group on students’ writing competence. It is proven by the result of descriptive analysis where the mean score of pre-test was 51.66 and mean score of post-test was 67.29. Furthermore, the result of hypothesis testing showed that the value of Sig (2-tailed) was 0.000 which smaller than alpha value 0.05, means that H0 is rejected and H1 is accepted. Therefore, it can be concluded that there is a significant effect of Peer Feedback through Facebook Group on upgrading students’ writing competence in recount text at MAN 1 Konawe Selatan. Hence, teaching and learning writing use Peer Feedback through Facebook Group can be one of effective methods on upgrading students’ writing competence.